A prior Magazine 14. - Roelandt, Els; Kreuger, Anders; Roelstraete, Dieter; Sinnig, Claudia; Piron, François; Rehm, Jean-Pierre; Harris, Larissa; Verwoert, Jan (Gent : vzw Mark; School of Arts Gent, 2007)
Augustijnen, Sven ; Koester, joachim ; Von Hauswolff, Carl Michael ; Narkevicius, Deimantas
Congo, Kolonisatie, Belgisch Congo, Lumumba, Kaliningrad
boek